Farmer perceptions of legumes and their functions in smallholder farming systems in east Africa - Muoni, Tarirai; Barnes, Andrew P.; Öborn, Ingrid; Watson, Christine A.; Bergkvist, Goran; Shiluli, Maurice; Duncan, Alan J. (Informa UK Limited, 2019)
Legumes play an important role in sub-Saharan Africa (SSA) farming systems through the provision of food, feed, fuel, income and a range of biophysical benefits, such as soil fertility enhancement and erosion control. However, their full potential is not being realized. The purpose of this study was to assess farmers' perceptions and knowledge towards legumes and the rationale of farmers for current legume production practices using a survey of 268 farmers in the Democratic Republic of Congo and Kenya. Most of the farmers had some knowledge of legumes and their characteristics. However, they had little knowledge of some key functions, including soil erosion control and soil fertility improvement. Most farmers relied on radio and other farmers for legume-related information. Farmers with relatively large livestock holdings ranked provision of livestock feed as an important legume function. We conclude that farmers put more value on short-term benefits of legumes including food and income than long-term benefits such as natural resource management and thus grain legumes are more readily identified by farmers than forage species. Also, we conclude that farmers require more than just information about legumes to increase uptake, they also require improved market access to procure inputs and sell products to realize other benefits that are associated with growing legumes.